Effectiveness of Behavioral Counseling Model of Modeling Techniques for Developing Self Exhibition - Gusti Agung aditya Nata Putra; I Ketut Dharsana; Ari Darmayanti (Department of Guidance and Counseling, FIP, Undiksha, 2017)
This research conducted at SMA LAB Undiksha Singaraja. The type that is